Atmospheric CO(2) effect on stable carbon isotope composition of terrestrial fossil archives - Hare, Vincent J. (Nat Commun, 2018)
The (13)C/(12)C ratio of C(3) plant matter is thought to be controlled by the isotopic composition of atmospheric CO(2) and stomatal response to environmental conditions, particularly mean annual precipitation (MAP). The effect of CO(2) concentration on (13)C/(12)C ratios is currently debated, yet crucial to reconstructing ancient environments and quantifying the carbon cycle. Here we compare high-resolution ice core measurements of atmospheric CO(2) with fossil plant and faunal isotope records. We show the effect of pCO(2) during the last deglaciation is stronger for gymnosperms (−1.4 ± 1.2‰) than angiosperms/fauna (−0.5 ± 1.5‰), while the contributions from changing MAP are −0.3 ± 0.6‰ and −0.4 ± 0.4‰, respectively. Previous studies have assumed that plant (13)C/(12)C ratios are mostly determined by MAP, an assumption which is sometimes incorrect in geological time. Atmospheric effects must be taken into account when interpreting terrestrial stable carbon isotopes, with important implications for past environments and climates, and understanding plant responses to climate change.